Bacteriological and Physicochemical Qualities of Ebutte River in Ebutte Community, Uhunmwonde Local Government Area, Edo State, Nigeria - Fred Osaro Ekhaise (Journal of Applied Sciences and Environmental Management)
The bacteriological and physicochemical qualities of Ebutte River in Ebutte Community were carried out to ascertain the variation in the quality of the river between August, 2010 and January, 2011. The bacteriological and physicochemical assessments were studied using the basic microbiological techniques. The bacterial counts were shown to be highest in the inhabited point (3) while downstream (points 4 and 5) and upstream (points 1 and 2) recorded lower counts due to little or no human activities. The bacterial counts were higher than the acceptable limit of the WHO standards at all sampling points. The total viable counts ranged from 3.40 x 105 to 3.71 x 106cfu/ml for the months of August, 2010 to January, 2011. The bacterial counts were showed to be highest in the rainy season. The total coliform counts ranged from 27MPN/100ml to 350MPN/100ml while the faecal coliform counts ranged from 5MPN/100ml to 26MPN/100ml. The faecal Streptococci counts were recorded to range from <2MPN/100ml to 14MPN/100 and the Clostridium counts ranges from <2MPN/100ml to 6MPN/100ml. The bacterial isolates isolated and characterised includes eleven bacterial genera among which are Escherichia, Klebsiella, Pseudomonas, Bacillus, Enterobacter, Streptococcus, Salmonella, Staphylococcus, Proteus, Clostridium and Shigella. The results of most of the physicochemical parameters analysed were shown to be higher at sampling point 3, which is the point that had direct effect of human activities. Similarly the values obtained for dissolved oxygen was shown to be lowest in the inhabited sampling point 3. Analysis of variance showed that there was a high significant difference (P<0.001) between total viable counts obtained in the two seasons while a significant difference (P<0.05) was obtained for total coliform counts and faecal coliform counts. Significant difference (P>0.05) was obtained for faecal Streptococci and Clostridium perfrigens counts. Correlation coefficient showed positive relationship between the total viable counts and some of the physicochemical parameters studied. The Ebutte River water quality studied based on the bacteriological and physicochemical parameters revealed that the human, animal and agricultural activities plays significant role in the contamination of the water source. @JASEM